Towards an augmented assistance dog - Rybarczyk, Yves (2015)
Despite the recent progresses in robotics, autonomous robots still have too many limitations to reliably help people with disabilities. On the other hand, animals, and especially dogs, have already demonstrated great skills in assisting people in many daily situations. However, dogs also have their own set of limitations. For example, they need to rest periodically, to be healthy (physically and psychologically), and it is difficult to control them remotely. This project aims to “augment” the service dog, by developing a system that compensates some of the dog weaknesses through a robotic device mounted on the dog harness. The present article shows that the dog’s activity and some indexes of the animal emotional state can be successfully identified by the wearable device. © Springer International Publishing Switzerland 2015.